PENGARUH MOTIVASI, DAN KOMPETENSI TERHADAP KINERJA KARYAWAN ALIH DAYA (OUTSOURCHING) DI PT. MULTI SARANA KARYA MANDIRI KARAWANG - Nurwulan Kusuma Devi; Amanda Rahayu Putri (Sekolah Tinggi Manajemen IMMI Jakarta, 2019)
The problem to be examined in this study is the performance of employees in outsourcing companies at PT. Multi Sarana Karya Mandiri Karawang. Estimating researchers are influenced by motivation and competence factors. How big is the influence of motivation and competence on the performance of outsourced employees at PT. Multi Sarana Karya Mandiri Karawang? The purpose of the authors conducted this study was to study and analyze the motivation and competence on the performance of outsourced employees at PT. Multi Sarana Karya Mandiri Karawang, and the magnitude of the influence of independent variables on the dependent variable. The method used in this study is a quantitative method using descriptive and verification approaches. Respondents to outsourchers PT. Multi Sarana Karya Mandiri Karawang as many as 60 people. The data in this study are primary and secondary data. Where the primary data obtained from respondents’ answers to the questionnaire distributed by the author. The results of the analysis of the data that has been done by the author, the results show that there is a positive and significant influence on motivation and competence on the performance of outsourched employees of PT. Multi Sarana Karya Mandiri Karawang with a correlation coefficient r value of 0.250 for motivation and 0.557 for competence with a strong degree and a regression model Y = 9,689 + 0,233 +0,501 X.